ENVIRONMENTAL MONITORING OF THE UNIVERSITY AS ONEOF THE COMPONENTS OF THE INTERNAL QUALITY ASSESSMENT SYSTEM - Natalia G. Bazhenova; Ekaterina L. Lutsenko (Высшее образование в России)
The quality of higher education is an essential foundation for creating a common educational space of the Russian Federation. Monitoring can be considered as one of the mechanisms for assessment the quality of the educational environment at the university, which allows to react promptly and to correct the arising problems.The paper presents the experience in conducting environmental monitoring research studies at the university, views the basic research areas according to the processes oforganizational life cycle, gives some data on certain issues.